PERAN GURU DALAM MENGEMBANGKAN EMOTIONAL INTELLIGENCE ANAK USIA 3-4 TAHUN - Sari, Dwi Indria; Nuria, Ratri (STKIP Persada Khatulistiwa Sintang, 2024)
This Research aims to identify the role of teachers in developing emotional intelligence in children aged 3-4 years and to determine the supporting and inhibiting factors in developing emotional intelligence. The research method used is a qualitative method with data collection techniques including observation, interviews, and documentation. The data analysis used in this research is data reduction, data display and conclusion drawing. The results of the research are: 1) The role of teachers in developing emotional intelligence in early childhood includes five aspects, a) recognizing oneself through a personal approach; b) managing children’s emotions can be done through role playing, discussing cause and effect, and learning the shiroh of the prophet Muhammad SAW; c) Motivating children is done by cultivating a sense of patience; d) Children’s Empathy is carried out through the habit of helping fellow friends, showing respect to friends, and respecting their friends; e) Socials skill are carried out through role playing or cooperative games. 2) The supporting factor is that fellow teachers must have the same principles; cooperation with parents, as well as outside teaching and learning or outing classes, while the inhibiting factors are teachers who are inconsistent, impatient and have no courage towards children.